Clostridium autoethanogenum protein inclusion in the diet for broiler: Enhancement of growth performance, lipid metabolism, and gut microbiota - Wu, Yushan; Wang, Jing; Jia, Ming; Huang, Shixin; Cao, Ying; Yao, Ting; Li, Junguo; Yang, Yuxin; Gu, Xu (Frontiers in Veterinary Science, 2022)
This study aimed to investigate the effects of dietary supplementation of the new single-cell protein Clostridium autoethanogenum protein (CAP) on growth performance, plasma biochemical indexes, liver histology, lipid metabolism, and gut microbiota in Cobb broilers. According to the randomized block experimental design, 960 Cobb broilers (1d old) were divided into six treatments with eight replicates of 20 birds each. Six isonitrogenous and isoenergetic diets were formulated with different contents of CAP (0, 1, 2, 3, 4, and 5%) to replace soybean meal (SBM). The results showed that the addition of CAP did not influence liver health when it exceeded 2%. The protein metabolism markers and feed conversion rate increased (P < 0.05), significantly improving the growth performance. When the content of CAP was greater than 4%, it could promote lipolysis without affecting lipogenesis, decreasing the abdominal fat rate. There was no significant difference in MDA between these groups (P = 0.948). The increase of SOD and GSH-Px indicated the enhancement of antioxidant response. Alpha diversity did not significantly differ between groups (P > 0.05). Inclusion of 4% or less CAP led to the increase in beneficial microbiota, the concentration of short-chain fatty acids (SCFAs) such as acetic acid, propionic acid, and butyric acid (P < 0.05), and the concentration of primary bile acids such as cholic acid and goose deoxycholic acid (P < 0.05). While the concentration of secondary bile acids such as taurocholic acid and taurine goose deoxycholic acid was decreased (P < 0.05). These results illustrated that the CAP had a high potential for application in poultry nutrition. In terms of improving growth performance and antioxidant capacity and reducing fat deposition rate, 4% CAP content is recommended.